Multicentre, randomised clinical trial of paediatric concussion assessment of rest and exertion (PedCARE): a study to determine when to resume physical activities following concussion in children. Issue 3 (12th July 2017) - Ledoux, Andrée-Anne; Barrowman, Nicholas J; Boutis, Kathy; Davis, Adrienne; Reid, Sarah; Sangha, Gurinder; Farion, Ken J; Belanger, Kevin; Tremblay, Mark S; Yeates, Keith Owen; DeMatteo, Carol; Reed, Nick; et al.
Abstract : Introduction: Rest until symptom-free, followed by a progressive stepwise return to activities, is often prescribed in the management of paediatric concussions. Recent evidence suggests prolonged rest may hinder recovery, and early resumption of physical activity may be associated with more rapid recovery postconcussion. The primary objective is to determine whether the early reintroduction of non-contact physical activity beginning 72 hours postinjury reduces postconcussive symptoms at 2 weeks in children following an acute concussion as compared with a rest until asymptomatic protocol. Methods and analysis: This study is a randomised clinical trial across three Canadian academic paediatric emergency departments. A total of 350 participants, aged 10–17.99 years, who present within 48 hours of an acute concussion, will be recruited and randomly assigned to either the study intervention protocol (resumption of physical activity 72 hours postconcussion even if experiencing symptoms) or physical rest until fully asymptomatic. Participants will document their daily physical and cognitive activities. Follow-up questionnaires will be completed at 1, 2 and 4 weeks postinjury. Compliance with the intervention will be measured using an accelerometer (24 hours/day for 14 days). Symptoms will be measured using the validated Health and Behaviour Inventory. A linear multivariable model, adjusting for site and prognostically important covariates, will be tested to determine differences between groups. The proposed protocol adheres to the RCT-CONSORT guidelines. Discussion: This trial will determine if early resumption of non-contact physical activity following concussion reduces the burden of concussion and will provide healthcare professionals with the evidence by which to recommend the best timing of reintroducing physical activities. Trial registration number: Trial identifier (Clinicaltrials.gov) NCT02893969 .